KOMPARASI PEMBAHARUAN ISLAM: Yudian Wahyudi dan Sayyid Ahmad Khan - Taqo Sidqi, Kholfan Zubair; Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2026)
This article compares Yudian Wahyudi with world figures. The goal is none other than the spirit of “winning the appeal (menang banding)” and “winning the match (menang tanding)” but not “fighting (perang tanding).” This article is a comparison of Islamic reform between Yudian Wahyudi and Sayyid Ahmad Khan regarding the idea of Islamic progress. Yudian Wahyudi and Ahmad Khan do indeed appear to be fellow modern Islamic reformers. There are certainly similarities, but it is precisely these differences that we certainly need to examine. At first glance, this article describes in detail the striking differences. However, Yudian Wahyudi seems to be more different than just an Islamic reformer. Why is that? Because his ideas, concepts, and thoughts are very new. That is the novelty of Yudian Wahyudi that Ahmad Khan does not have, considering that Yudian Wahyudi himself has written about Ahmad Khan with the title: Al-Afghani and Ahmad Khan on Imperialism: A Comparison from the Perspective of Islamic Legal Philosophy. Therein, the advantages and differences that other thinkers have not yet discovered are discovered. One of the novelties of his thinking, Yudian Wahyudi advocated the need for experimental sciences in Islamic education, particularly in the Islamic boarding schools (pesantren) and Sufi orders (tarikat).